Faking liberties: religious freedom in American-occupied Japan - Thomas, Jolyon Baraka (Class 200: new studies in religion, 2019)
Prologue: the drums of war -- Conventions -- Introduction: the universal particularity of religious freedom -- A preoccupation with religious freedom -- The Meiji constitutional regime as a secularist system -- Who needs religious freedom? -- Domestic problems, diplomatic solutions -- In the absence of religious freedom -- The occupation of religious studies -- State shinto as a heretical secularism -- Who wants religious freedom? -- Universal rights, unique circumstances -- Out of the spiritual vacuum -- Conclusion: the bellicose pacifism of religious freedom -- Epilogue: songs of freedom